Psychometric Evaluation of the Czech Version of Group Cohesiveness Scale (GCS) in a Clinical Sample: A Two-Dimensional Model - Klocek, Adam; Řiháček, Tomáš; Cígler, Hynek (Frontiers in Psychology, 2020)
The Group Cohesiveness Scale (GCS, 7 items) measures patient-rated group cohesiveness. The English version of the scale has demonstrated good psychometric properties. This study describes the validation of the Czech version of the GCS. A total of 369 patients participated in the study. Unlike the original study, the ordinal confirmatory factor analysis (CFA) supported a two-dimensional solution (RMSEA = 0.075; TLI = 0.986). The analysis demonstrated the existence of two moderately to highly associated (r = 0.79) domains of group cohesiveness—affective and behavioral. The two-dimensional model was invariant across genders, age, education, and time (retest after 6 weeks) up to factor means level. Internal consistency reached satisfactory values for both domains (affective, ω = 0.86; behavioral, ω = 0.81). In terms of convergent validity, only weak association was found between the GCS domains and the group working alliance measured by the Group Outcome Rating Scale (GSRS). This is the first revision of the factor structure of the GCS in the European context. The scale showed that the Czech version of the GCS is a valid and reliable brief tool for measuring both aspects of group cohesiveness.